SOME STRATEGIES TO DO READING COMPREHENSION EXERCISES EFFECTIVELY FOR NON-ENGLISH MAJORED FRESHMEN AT TAY DO UNIVERSITY IN VIET NAM - NGUYEN, Nga H.T. (2023)
Among four skills in language, reading has a key role which is a basic means to improve other skills. Without reading, it is difficult for students to further their advanced education in higher levels. The study was conducted to find out the methods to do reading comprehension exercises effectively and quickly as well as some suggestions to improve reading skill for non-English majored freshmen at Tay Do University. The participants were of 102 non-English majored freshmen majoring in Pharmacy, Accounting, Business Administration, Food Technology, and Information Technology. The instruments were questionnaire to get the information and the reading test to evaluate students’ levels in reading comprehension using skimming, scanning, guessing the meanings of words from context and background knowledge to do “True/False”, “Question types”, “Filling in the blank” and “Matching” exercises.